MAINTAINING INEQUALITY IN CONSUMPTION: GOVERNMENT LED EDUCATION PROCESS FAIRNESS AND SHADOW EDUCATION PRODUCT CONSUMPTION - Meng , QingJiao; Jiang , Luo; Fan, Mengqi (Journal of Economic Education, 2025)
This study examines whether government initiatives aimed at promoting educational equity in China may be weakened or counteracted by forces that sustain or recreate educational inequality. Although recent policies such as the cancellation of demonstration schools and the implementation of the “double reduction” policy seek to reduce disparities, theories of Maximally Maintained Inequality (MMI) and Effectively Maintained Inequality (EMI) suggest that socioeconomically advantaged families often adopt strategic behaviors to preserve their competitive edge. Using data from the 2014–2015 China Education Panel Survey (CEPS), this study analyzes 10,751 eighth-grade students and employs both OLS and Probit regression models to assess how educational costs and educational balance influence families’ choices regarding shadow education products. The results indicate that even when opportunities appear more equal, high-SES families continue to obtain advantages through selective and resource-driven participation in shadow education, thereby sustaining existing inequalities. Furthermore, policies intended to reduce educational costs and promote fairness have unintentionally encouraged greater consumption of shadow education services, leading to new forms of inequality. These findings highlight that government-driven efforts to achieve educational equity may be undermined by persistent consumption-based mechanisms of inequality, suggesting that current reforms may be insufficient to fully realize equitable educational outcomes